Recovery of silica-free tantalum from epoxy-coated tantalum capacitors using hydrometallurgical routes - Agrawal M.; Singh R.; Singh K.K. (My University, 2025)
Scarcity of natural resources along with rising demand for tantalum from the capacitor and superalloy sector has made it a critical metal. Increasing pressure on consistent supply is a growing concern for user industries. Waste tantalum capacitors as a secondary resource, may help to conserve the natural resources and minimize the waste generation if processed efficiently. Recycling tantalum from capacitor is extremely difficult due to its complex design and uneconomic recovery methods. In this article, recovery of tantalum was undertaken following two different hydrometallurgical routes. In each of the process, epoxy coated tantalum capacitor is first subjected to the pre-processing stage to liberate tantalum-rich concentrate, followed by acidic/alkaline leaching and subsequent purification (if needed) of the resultant product to generate high purity tantalum product. Performance of both processes is evaluated and compared on the basis of percentage recovery of tantalum and the number of steps involved to yield the desired final product. Moreover, there are processes marred by the presence of silica in the encapsulating material of capacitor, however, in here we have completely separated silica with the organic matter in the pre-processing stage to produce silica-free tantalum-rich concentrate, without any need of costly and energy-consuming method. Both processes can recover high-purity tantalum from capacitors. However, the recovery in the two-stage acidic leaching route was near to 98% - much higher than the alkaline one (70%) - due to the formation of insoluble tantalum concentrate in the alkaline process. © 2022 Elsevier Ltd.